Através das fachadas: a projeção mapeada em Arquitetura e seus possíveis desdobramentos espaciais - Wanderson Garcia (2013)
This dissertation approaches the social-spatial transformations occurred in the city of Belo Horizonte, focusing in a recent imagetic technology, called Architectural Projection Mapping, in order to understand how urban interventions have been promoting citizens construction of public spaces. For that, the study proposes three main discussion niches: the first set on a conceptual basis, in order to form a coherent and stimulating theoretical platform for the comprehension of this universe; a second one, directed to the analysis of historical cases which would contribute to understand the imagetic problems when dealing with urban problematic spatiality; and a third moment, consisting on study cases. Two paradigmatic cases are studied in depth, followed by a thorough analysis on the Belo Horizonte scenario, and the professional knowledge of two important representatives from São Paulo. Following the cases analysis, the study defines current trends of this universe in its relationship with the city, highlighting divergent developments. It concludes, on the one hand, that it exists the possibility where these technologies could introduce transformations of character citizen to the city. On the other hand, it reveals an opposite trend: the obstacle presented by the marketing pressure on such events, resulting on the negation of everyday citizens practices.